ANALISIS MUATAN HOTS (HIGER ORDER THINKING SKILLS) PADA BUKU TEKS SISWA PENDIDIKAN AGAMA KRISTEN DAN BUDI PEKERTI KELAS VII TERBITAN KEMENDIKBUD EDISI REVISI 2017HOTS (Higher Order Thinking Skill) is a thinking process of students at a higher cognitive le - Steaven Octavianus; Winda Listiana; Reni Triposa (TANGKOLEH PUTAI, 2021)
HOTS (Higher Order Thinking Skill) is a thinking process of students at a higher cognitive level. The main goal of HOTS is to hone the thinking skills of students at a higher level, related to the ability to think critically, creatively, solve problems, and make decisions in complex situations. The student book on Christian Religious Education and Characteristics for SMP class VII published by the Ministry of Education and Culture, the 2017 revised edition is a book intended for students as a guide in learning activities. From the results of data analysis, it shows that HOTS content that appears most in textbooks is to analyze (C4) 46, 07% then create (C6) 33, 34% and the least evaluate (C5) 20, 58%. Therefore, the book is stated to follow the needs of junior high school students because it contains more cognitive abilities to analyze than other cognitive abilities. However, when viewed from the cognitive level, the book is not coherent because it produces (C6) more than evaluates (C5). Keywords: HOTS, Student Textbooks